Kisspeptin-neuron control of LH pulsatility and ovulation - Stevenson, Harvey; Bartram, Samuel; Charalambides, Mikaela Maria; Murthy, Sruthi; Petitt, Theo; Pradeep, Anjali; Vineall, Owen; Abaraonye, Ikenna; Lancaster, Amelia; Koysombat, Kanyada; Patel, Bijal; Abbara, Ali (Frontiers in Endocrinology, 2022)
Kisspeptin is a neuropeptide produced by hypothalamic neurons that co-express Neurokinin B and Dynorphin and are thus termed ‘Kisspeptin-Neurokinin B-Dynorphin’ (KNDy) neurons. Kisspeptin has been identified as a key player in the central mechanisms regulating the menstrual cycle, the hypothalamic-pituitary-gonadal (HPG) axis, and reproduction. It is well established that the hypothalamic estrogen receptor (ERα), present in differing cell populations between mammalian species, controls the release of kisspeptin through both positive and negative feedback mechanisms. In more recent times, KNDy neurons expressing ERα have been identified as the GnRH pulse generator involving both positive and negative feedback loops, governing the release of GnRH which in turn mediates both LH pulsatility and the timing of the LH surge. The pulse generator can be modulated by various factors including glutamate, leptin and estrogen. This review will delve into the role of kisspeptin neurons in both the arcuate nucleus (ARC) and the anteroventral periventricular (AVPV) nucleus, which together act as hubs for mediating both estrogen negative feedback associated with LH pulsatility, and estrogen positive feedback associated with the preovulatory LH surge and consequent ovulation. This has been confirmed by studies, which reveal that when the ERα is activated, it can upregulate Kiss1 expression in the AVPV-kisspeptin neurons and downregulate Kiss1 expression in ARC-kisspeptin neurons. Furthermore, this review covers the mechanisms determining Kiss1 expression and further pathways involved in governing LH pulsatility and the preovulatory LH surge. Unravelling these mechanisms will prove useful in developing future therapies for reproductive disorders.